Health education about hypertension to increase knowledge for senior citizens - Andi Suyatni Musyrah; Deviarbi Sakke Tira; Nordianiwati Nordianiwati; Lumastari Ajeng Wijayanti; Marisca Jenice Sanaky; Muhammad Dawam Jamil (Journal Pengabdian Masyarakat Politeknik Sandi Karsa, 2024)
Hypertension is a health problem that often occurs in senior citizens and can increase the risk of heart disease, stroke, and other health complications. Health education about hypertension among senior citizens has become very important to improve their understanding of this condition. The purpose of this activity is to implement health promotion and preventive efforts based on collaboration between professions in providing hypertension health education to the elderly. The method used is material presentation, discussion, and evaluation of activities. The result of the implementation of this activity is an increase in elderly knowledge about hypertension from poor to good. It was concluded that there was a need for periodic socialisation involving many communities and cadres. Families are expected to apply at home and disseminate information related to hypertension. Through this increased knowledge, it is hoped that senior citizens can take preventive and proactive steps in managing their blood pressure, promoting heart health, and improving their overall quality of life. This holistic approach involves collaborating with health workers, drawing on local resources, and ensuring social support is in place to support efforts to prevent and manage hypertension among senior citizens